2017
DOI: 10.31529/sjms.2017.3.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pay Satisfaction, Job Stress, and Abusive Supervision on Turnover Intention among Banking Employees

Abstract: Pakistan banks cannot survive well without trained and experienced employees. Many researchers have reported the high turnover in banking sector. Therefore it was highly important to address this problem. The purpose of this study was to test the factors (pay satisfaction, job stress, and abusive supervision) influencing turnover intention among bank employees. This study collected the data from a sample of 100 bank employees both public and private banks in Vehari. The results showed that there was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
(24 reference statements)
2
12
0
2
Order By: Relevance
“…Regarding the relation of POS and stress previous studies found negative relation which is in line with our finding [32,[41][42][43][44][45][46][47]. Finally, we also have previous studies regarding stress and TI which most of them found positive relationship [12,13,[53][54][55][56][57][58]. Our model based on these studies.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the relation of POS and stress previous studies found negative relation which is in line with our finding [32,[41][42][43][44][45][46][47]. Finally, we also have previous studies regarding stress and TI which most of them found positive relationship [12,13,[53][54][55][56][57][58]. Our model based on these studies.…”
Section: Resultssupporting
confidence: 89%
“…Other studies from Korea using participants from hotel and hospitals support findings that work-related stress can predict employee intentions to quit [53,54]. Other studies also had found the same result [55][56][57][58]. A positive relationship underlies the relation between work-stress and TI.…”
Section: Stress and Turnover Intentionmentioning
confidence: 72%
“…So, employees' PS might not relate to ETP (Edwards et al, 2008). PS in the absence of MS has a weak relation to employee outcomes (i.e., performance, turnover, commitment) (Bhatnagar, 2014;Raza et al, 2017).…”
Section: The Moderating Role Of Msmentioning
confidence: 99%
“…Research conducted by Quresi et al (2013) on the textile industry in Pakistan also showed that job stress and turnover intentions have a significant positive Yag Sewwandi and Perere (2016) conducted a study of the apparel industry in Sri Lanka the results obtained from this research that job stress and turnover intention positive significant effect. Research Raza et al (2017) in the banking industry in Pakistan also shows a positive result of the relationship between job stress and turnover intention of employees.…”
Section: Job Stress and Turnover Relationship Itentionmentioning
confidence: 94%